EVALUASI PENENTUAN BAGI HASIL DAN KELAYAKAN FINANSIAL PENGELOLAAN HUTAN BERSAMA MASYARAKAT DI KESATUAN PEMANGKUAN HUTAN KEDU UTARA (Studi Kasus di RPH Leksono, BKPH Wonosobo) - , PRIHANANTYO IRAWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The Community-Based Forest Management (CBFM) has been applied in Perum Perhutani area including in KPH Kedu Utara is an appropriate forest management strategy. The aim of this research is to determine profit sharing profile between two parties with cultivated plant species pine (Pinus merkusii) and salak (Salacca edulis). The total number of respondents that work as farmers in this research is 30 with level of land area management (land plot) between 0.25 ha (1 plot) up to 1 ha (4 plot). The results of this research can be described as follow: (1) Profit sharing of pine forest are equal to Rp 49.278.484,00/ha/cycle (76,76%) for KPH Kedu Utara and Rp15.768.844,00/ha/cycle (24,24%) for farmers